Penguatan Sistem Imun Dalam Menghadapi Pembelajaran Luring Untuk Guru SMP Negeri 1 Tegalampel Bondowoso - Santika Rentika Hadi; Hayati; Muhammad Wahyono; Moh Hanfi; Brahmana Rangga; Billy Emir Rizkanto (Kanigara, 2022)
In order to prepare for offline learning, SMPN 1 Tegalampel Bondowoso needs many references on how to improve the immune system in the pandemic era to avoid covid-19. Starting from knowledge about immunity. Therefore, it is necessary to hold counseling about the immune system at SMPN 1 Tegalampel Bondowoso. The implementation of the Community Service Program activities by the Physical Education Lecturer Team at PGRI Adi Buana University Surabaya went smoothly. The teachers of SMPN 1 Tegalampel Bondowoso were very enthusiastic about participating in every scheduled activity. In order to prepare for offline learning, SMPN 1 Tegalampel Bondowoso needs many references on how to improve the immune system through exercise in the pandemic era to avoid covid-19. Starting from knowledge about immunity, increasing immunity by improving nutrition, increasing immunity by exercising and other knowledge that can benefit everyone